No place like home: A national study on firearm-related injuries in the American household - Napaporn Kongkaewpaisan (2020)
© 2020 Elsevier Inc. Background: We aimed to examine the prevalence of, and describe factors associated with, firearm-related injuries in American households. Methods: Using the 2010–2016 ACS-TQIP database, all ICD-9/10 external causes of injury for firearm-related injuries were queried with the place of occurrence designated as “home”. Causes of injury were identified as assault, intentional self-injury, and unintentional injury. Univariate then multivariable regression analyses were performed to identify factors associated with each injury type. Results: 12,657 firearm-related injuries in households were identified. Of those, 49.9% were victims of assault, 35.7% were intentional self-injury, and 14.4% were unintentional. Mortality was highest among self-inflicted injuries (52.4%), followed by assault (12.9%), and unintentional injuries (5.9%). On multivariable analysis, age <45 years, African-American race, and drug use were independently associated with an injury secondary to assault. Age >65 years, White race, psychiatric illness, and alcohol use disorder were independently associated with intentional self-injury. White and American-Indian race were independently associated with unintentional injuries. Conclusions: Assault is the most common cause of home-related firearm injury requiring hospitalization, while intentional self-injury is the most lethal.